High throughput transcriptomics analysis of ovine mammary epithelial cells stimulated with Staphylococcus aureus in vitro - Saif Adil Abbood Al-Janabi; Ghulam Asghar Sajid; Sidra Zeb; Muhammad Jasim Uddin; Mehmet Ulas Cinar (PLoS ONE, 2025)
In sheep, the innate immune response of mammary epithelial cells (MECs) plays a central role in combating mastitis, yet our understanding of their resistance mechanisms remains limited. This study aimed to elucidate the gene expression profiles of ovine MECs following in vitro stimulation with Staphylococcus aureus (S. aureus) using RNA-Seq technology. Bioinformatics analysis identified a total of 175 differentially expressed genes (DEGs), including 172 up-regulated and 3 down-regulated genes in the stimulated group compared to the non-stimulated control group. Gene ontology annotation and functional pathway analysis indicated that these DEGs are primarily involved in ribosomal functions, which are essential for protein synthesis and first target of pathogens, as well as in immune response dysregulations, infection, phagocytosis, and bacterial invasion of epithelial cells. Validation via quantitative real-time PCR (qRT-PCR) confirmed the RNA-Seq results. Our results revealed that DEGs converged on innate immune pathways (TLR, NOD-like receptor, NF-κB, MAPK), cytoskeletal remodeling and translational control, indicating inflammatory activation and cell injury in oMECs and highlighting candidate targets for mastitis resistance selection against S. aureus. These findings significantly contribute to the understanding of how ovine MECs respond to S. aureus stimulation, providing a foundation for further research, particularly regarding the immune defense mechanisms, strategies and implications in dairy industry.